Perencanaan Pembelajaran Digital IPS di Sekolah Dasar: Integrasi Model Berbasis Keterampilan Abad 21 - Mu'minatul Habibah; Atika Muallifah; Faldin Baen; Nuzulus Sa’adatun Nisa; Siti Nur Fikriyah; Dede Ajeng Arini (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
This study aims to analyze digital learning planning for Social Studies (IPS) in elementary schools and examine the development of 21st-century skills-based learning models. This study employed a literature review approach, reviewing relevant scientific articles from the past five years. Data was obtained through a search of academic databases and analyzed using content analysis techniques to identify concepts, patterns, and research findings related to digital learning and 21st-century skills. The study's results indicate that digital learning plays a crucial role in improving the quality of social studies learning. The use of technology such as interactive media, instructional videos, and digital platforms has been shown to increase student motivation, engagement, and learning outcomes. Furthermore, the integration of technology into learning also supports the development of 21st-century skills, such as critical thinking, creativity, collaboration, and communication. Learning models such as Problem-Based Learning and Project-Based Learning are considered effective in integrating technology with active and contextual learning activities. However, the implementation of digital learning still faces various obstacles, such as limited teacher competency, unequal access to technology, and suboptimal lesson planning. Therefore, systematic learning planning and improving teachers' digital competencies are necessary to ensure effective technology utilization. In conclusion, digital learning planning in elementary school social studies needs to be developed in a structured manner, integrating technology and 21st-century skills. This research is expected to contribute to the development of more effective, innovative learning models that meet the demands of education in the digital age.